Irvsp: To obtain irreducible representations of electronic states in the VASP - Gao, Jiacheng; Wu, Quansheng; Persson, Clas; Wang, Zhijun (Computer physics communications, 2021)
We present an open-source program irvsp, to compute irreducible representations of electronic states for all 230 space groups with an interface to the Vienna ab-initio Simulation Package. This code is fed with plane-wave-based wavefunctions (e.g. WAVECAR) and space group operators (listed in OUTCAR), which are generated by the VASP package. This program computes the traces of matrix presentations and determines the corresponding irreducible representations for all energy bands and all the k-points in the three-dimensional Brillouin zone. It also works with spin–orbit coupling (SOC), i.e., for double groups. It is in particular useful to analyze energy bands, their connectivities, and band topology, after the establishment of the theory of topological quantum chemistry. Accordingly, the associated library – irrep_bcs.a – is developed, which can be easily linked to by other ab-initio packages. In addition, the program has been extended to orthogonal tight-binding (TB) Hamiltonians, e.g. electronic or phononic TB Hamiltonians. A sister program ir2tb is presented as well. Program title: irvsp CPC Library link to program files:https://doi.org/10.17632/y9ds5nnm2f.1 Licensing provisions: GNU Lesser General Public License Programming language: Fortran 90/77 Nature of problem: Determining irreducible representations for all energy bands and all the k-points in 230 space groups. It is in particular useful to analyze energy bands, their connectivities, and band topology. Solution method: By computing the traces of matrix presentations of space group operators for the eigen-wavefunctions at a certain k-point in a given space group, one can determine irreducible representations for them.